2021
DOI: 10.1186/s12889-021-11244-3
|View full text |Cite
|
Sign up to set email alerts
|

Core health-components, contextual factors and program elements of community-based interventions in Southeast Asia – a realist synthesis regarding hypertension and diabetes

Abstract: Background In Southeast Asia, diabetes and hypertension are on the rise and have become major causes of death. Community-based interventions can achieve the required behavioural change for better prevention. The aims of this review are 1) to assess the core health-components of community-based interventions and 2) to assess which contextual factors and program elements affect their impact in Southeast Asia. Methods A realist review was conducted, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The results showed that adolescents with normal blood pressure were 31 respondents (70.5 %), while an increase in blood pressure was 13 respondents (29.5 %). There was a significant relationship between smoking (OR =0.173, 95 % CI 0.038-0.785, p-value 0.016) and a history of alcohol consumption (OR= 4,000, with an increase in blood pressure in adolescents. Gender, family history of hypertension, physical activity, and a high salt diet did not have a significant relationship with an increase in blood pressure in adolescents with a p-value > 0.05.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that adolescents with normal blood pressure were 31 respondents (70.5 %), while an increase in blood pressure was 13 respondents (29.5 %). There was a significant relationship between smoking (OR =0.173, 95 % CI 0.038-0.785, p-value 0.016) and a history of alcohol consumption (OR= 4,000, with an increase in blood pressure in adolescents. Gender, family history of hypertension, physical activity, and a high salt diet did not have a significant relationship with an increase in blood pressure in adolescents with a p-value > 0.05.…”
Section: Resultsmentioning
confidence: 95%
“…Hypertension is a growing problem and might be happened at all periods of age (1,2). Hypertension is a long-term health problem and a leading cause of premature death in adults worldwide, including in developed and developing countries (3)(4)(5)(6). Unfortunately, hypertension in children and adolescents is often neglected and continues into adulthood (7).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this guideline can be more widely applied to other CBHIs and in other countries. Furthermore, as indicated in the literature, a guideline with a checklist for contextual adaptation of CBHIs can lead to more effective interventions to promote health [1,[4][5][6], but not only health. All stakeholders indicated that the usefulness of this guideline extends beyond health-related communitybased interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In Southeast Asia, community-based health interventions (CBHIs) are often implemented to target non-communicable diseases (NCDs) [1][2][3]. There is some indication that CBHIs-that are tailored to sociocultural aspects of health and well-being: local language, religion, customs, traditions, individual preferences, needs, values, and interests-may promote health more effectively than when no attention is paid to these aspects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation